PROGRAM GERAKAN LITERASI SEKOLAH (GLS) PERLU DUKUNGAN KEPALA SEKOLAH - Mahendrartha, Azizul; Tobari, Tobari; Tohirin, Tohirin; Harnadi, Harnadi (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2020)
Abstract—Principal has a very important role in school management. High and low quality of the school can not be separated from the role of the Principal. Qualified or professional principals are able to show good performance and have an impact on improving the quality of the school they lead, therefore it is highly demandedby the principal's support in managing and managing all available resources including managing the School Literacy Movement (GLS) program. The purpose of this study was to determine the School Literacy Movement Program (GLS) in SMP Negeri 9 Prabumulih and the support given by the school principal. This research is a type of qualitative research with data collection techniques in the form of observation, documentation, and interviews. The effort to implement literacy has been developed by the Head of SMP Negeri 9 Prabumulih by various ways including the program to enter the library once a week, collection of books in the library, reading corners, making reading halls, wall magazines, selection of reading ambassadors, and putting up posters about literacy and bring a mobile library from the Prabumulih City Library. The School Literacy Movement (GLS) program has been running well even though it still requires more tangible and continuous follow-up. The benefits of this research are in addition to knowledge, references or contributions of ideas to add insight into the world of education. Keyword—-School Literacy Movement (GLS), school principal support Abstrak—Kepala Sekolah memiliki peran yang sangat penting dalam pengelolaan sekolah. Tinggi rendahnya kualitas sekolah tidak lepas dari peran Kepala Sekolah. Kepala Sekolah yang berkualitas atau profesional mampu menunjukkan kinerja yang baik dan berdampak pada meningkatnya kualitas sekolah yang dipimpinnya, karena itu sangat dituntut dukungan kepala sekolah dalam mengatur dan mengelola semua sumber daya yang ada termasuk mengelola program Gerakan Literasi Sekolah (GLS).Tujuan penelitian ini adalah untuk mengetahui Program Gerakan Literasi Sekolah (GLS) di SMP Negeri 9 Prabumulih serta dukungan yang diberikan kepala sekolah.Penelitian ini merupakan jenis penelitian kualitatif dengan teknik pengumpulan data berupa observasi, dokumentasi, dan wawancara.Upaya pelaksanaan literasi sudah dikembangkan oleh Kepala SMP Negeri 9 Prabumulih dengan melakukan berbagai cara yaitu antaralain programmasuk perpustakaa nsetiap satu minggu sekali, koleksi buku di perpustakaan, pojok baca, membuat pondok baca, majalah dinding, pemilihan duta baca, dan memasang poster tentang literasi serta mendatangkan perpustakaan keliling dari Perpustakaan Kota Prabumulih. Program Gerakan Literasi Sekolah (GLS) ini telah berjalan dengan baik meskipun begitu masih memerlukan tindak lanjut yang lebih nyata dan berkesinambungan. Manfaat penelitian ini adalah sebagai tambahan ilmu pengetahuan,rujukanatausumbangan pemikiran untuk menambah wawasan dalam dunia pendidikan. Kata Kunci—Gerakan Literasi Sekolah (GLS), dukungan kepala sekolah